2013
DOI: 10.1111/ejn.12114
|View full text |Cite
|
Sign up to set email alerts
|

Intermittent nicotine exposure upregulates nAChRs in VTA dopamine neurons and sensitises locomotor responding to the drug

Abstract: Dopaminergic projections from the ventral tegmental area (VTA) to the nucleus accumbens (NAcc) mediate the behavioral and motivational effects of many drugs of abuse, including nicotine. Repeated intermittent administration of these drugs, a pattern often associated with initial drug exposure, sensitizes the reactivity of dopamine (DA) neurons in this pathway, enhances the locomotor behaviors the drugs emit, and promotes their pursuit and self-administration. Here we show that activation of nicotinic acetylcho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 48 publications
(83 reference statements)
2
24
0
Order By: Relevance
“…This GluR2-lacking receptor pool typically displays inward rectification (Isaac et al, 2007;Liu and Zukin, 2007), and one study confirms the appearance of this type of AMPAR after a single exposure to nicotine (Gao et al, 2010). Another study on nicotine (Baker et al, 2013) exposure to VTA DA neurons, however, demonstrated increases in AMPA/NMDA ratios but no appearance of an AMPAR pool displaying inward rectification. We find no appearance of inward rectification in AMPA-evoked currents (Fig.…”
Section: Discussionmentioning
confidence: 92%
“…This GluR2-lacking receptor pool typically displays inward rectification (Isaac et al, 2007;Liu and Zukin, 2007), and one study confirms the appearance of this type of AMPAR after a single exposure to nicotine (Gao et al, 2010). Another study on nicotine (Baker et al, 2013) exposure to VTA DA neurons, however, demonstrated increases in AMPA/NMDA ratios but no appearance of an AMPAR pool displaying inward rectification. We find no appearance of inward rectification in AMPA-evoked currents (Fig.…”
Section: Discussionmentioning
confidence: 92%
“…For instance, intermittent exposure to drug achieved via experimenter-administered i.p. injections of cocaine (Downs and Eddy, 1932, Post, 1980, Post and Rose, 1976, Reith et al, 1987and Stewart and Badiani, 1993 or nicotine (Baker et al, 2013 andDi Chiara, 2000) more readily induces sensitization to the psychomotor activating effect of these drugs, while continuous infusion produces tolerance to this effect. Fig.…”
Section: Preclinical Studies Show That Drug Pharmacokinetics Determinmentioning
confidence: 99%
“…Recently, it has been demonstrated that intermittent exposure to nicotine (one dose on alternate days) does evoke a transient (hours) functional upregulation of AChRs in VTA dopaminergic neurons (Baker et al, 2013). This work also documented that intermittent nicotine exposure produced no functional upregulation on VTA GABAergic neurons.…”
Section: Upregulation Of Achrs Depends On Achr Subtypementioning
confidence: 99%